Pelatihan kreasi minuman kopi bagi masyarakat desa Lengkong Kulon - Ringkar Situmorang; Yoanita Alexandra; Septi Fahmi Choirisa (Jurnal Sinergitas PKM & CSR, 2023)
Lengkong Kulon Village is one of the villages that have the potential to become a leading tourist village in the province of Banten. The town is located in the Pagedangan sub-district. Community Service is carried out to help village communities cultivate ten empty kiosks to sell products in the culinary business. This activity was proposed by BUMDES (Village Owned Enterprise) of Lengkong Kulon Village. The training focused on basic teaching methods regarding coffee, basic manual brewing techniques, and the famous creation of coffee menus. The training is to broaden the knowledge of the local community regarding the potential coffee business in the area. The 20 participants of this training come from the youth group of Lengkong Kulon. The training is carried out at the Multimedia Nusantara University (UMN) Campus. Activities implemented in several stages include preparation for service, implementation of service, data collection; the result of seminars; and writing the report. The results of this activity received lively enthusiasm from the local village communityabstract in bahasaDesa Lengkong Kulon adalah salah satu desa yang mempunyai potensi menjadi desa unggulan wisata di provinsi Banten. Desa yang berada di kecamatan Pagedangan. Pengabdian Kepada Masyarakat dilaksanakan untuk membantu masyarakat desa membudidayakan 10 gerobak kosong untuk keperluan penjualan produk di bidang kuliner, sesuai dengan permintaan dari BUMDES (Badan Usaha Milik Desa) Desa Lengkong Kulon. Pelatihan difokuskan pada cara pengajaran dasar mengenai kopi, teknik dasar manual brewing coffee, dan juga kreasi menu kopi, yang diharapkan akan memperluas wawasan masyarakat Desa Lengkong Kulon akan potensi bisnis kopi, serta cara pembuatannya.  20 peserta pelatihan ini datang dari kelompok pemuda karang taruna desa Lengkong Kulon. Pengabdian dilaksanakan secara off-line di Kampus Universitas Multimedia Nusantara (UMN). Kegiatan dilakukan pada beberapa tahap meliputi (1) persiapan pengabdian; (2) pelaksanaan pengabdian; (3) pengumpulan data; (4) seminar hasil pengabdian; dan (5) penulisan laporan pengabdian. Hasil dari aktivitas ini mendapatkan antusiasme yang meriah dari masyarakat desa setempat.